Annual report on education spending in England: 2023 - Elaine Drayton; Christine Farquharson; Kate Ogden; Luke Sibieta; Imran Tahir; Ben Waltmann (Institute for Fiscal Studies (IFS), 2023)
Our sixth annual report on education spending shows changes over time across different stages of education, as well as geographic differences.
Keywords: 330; Education and skills; Government finances and spending; Education spending; Education; Childcare and early years; Schools; Higher education; Further education; Government spending; Geography; COVID-19; Early childhood development; Inflation